2018
DOI: 10.1111/iej.13019
|View full text |Cite
|
Sign up to set email alerts
|

Direct and transdentinal biostimulatory effects of grape seed extract rich in proanthocyanidin on pulp cells

Abstract: Aim To evaluate the potential biostimulatory effects of grape seed extract (GSE) on a primary culture of human pulp cells. Methodology Human molars were used to obtain the primary pulp cell culture and 0.5‐mm dentine discs. For GSE direct exposure, dose–response (0.0065–6.5%) and time response (1–60 min of contact) were examined. For transdentinal exposure, 0.65% of GSE was tested for 24 h. Cellular metabolism, nitric oxide and collagen production, and cell morphology alterations were assessed at periods of 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
7
1
1
Order By: Relevance
“…In addition, the extract increased ALP deposition significantly in both cell lines. Our results differ from those of Santos et al 13 , who evaluated the culture of human pulp cells from third molars, and observed no difference in ALP production between the control and the group exposed to the extract. According to these authors, this could be explained by the contact time with the grape extract made only on the last day of differentiation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, the extract increased ALP deposition significantly in both cell lines. Our results differ from those of Santos et al 13 , who evaluated the culture of human pulp cells from third molars, and observed no difference in ALP production between the control and the group exposed to the extract. According to these authors, this could be explained by the contact time with the grape extract made only on the last day of differentiation.…”
Section: Discussioncontrasting
confidence: 99%
“…11 Park et al 12 observed that in vivo administration of GSE improved the arthritic manifestations of collagen-induced arthritis (CIA) in mice, simultaneously suppressing in vitro osteoclast differentiation and promoting in vitro osteoblast differentiation. When investigating the early effects of GSE on cells derived from pulp tissue, Santos et al 13 observed that low concentrations of GSE were associated with an increase in cell viability, decreased production of nitric oxide, and increased synthesis of extracellular matrix by pulp cells from human third molars.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained discs were then subjected to a specific treatment protocol. Both sides of the discs were treated with 0.5 M EDTA solution for a duration of 60 s, followed by thorough rinsing with distilled water to remove any residual EDTA 74 . Subsequently, discs were individually wrapped in surgical-grade paper and sterilized in an autoclave (saturated steam under pressure).…”
Section: Methodsmentioning
confidence: 99%
“…A disc of each tooth was obtained, and all adjacent enamel was removed. Discs were treated with 0.5 mol L −1 EDTA for 60 s for both sides and then washed with distilled water (Dos Santos et al, 2019). Subsequently, the discs were individually wrapped and sterilized in an autoclave (saturated steam under pressure).…”
Section: Mature Antibiofilm Activitymentioning
confidence: 99%